Efficiency of Plant Growth Promoting Rhizobacteria (PGPR) Consortia for Modulation of Phytohormone and better Nutrient Acquisition - Mogal, Chaitanya S; Jha, Sanjay; Suthar, Harish; Parekh, Vipulkumar; Rajkumar, B K (Plantae Scientia, 2020)
Utilization of plant growth promoting Rhizobacteria (PGPR) as suitable substitute to chemical fertilizers and also in command to promote the plant growth. Five potential strains were studied for multifarious PGP traits viz. Indole-3-acetic acid (IAA), phosphate (P) solubilization, siderophore production, ammonia production, production of 1-Aminocyclopropane-1-carboxylate deaminase (ACC), phytohormone production, exhibiting antifungal activity etc. All five strains were resulted to have multifarious PGP traits. 2 Consortium were prepared using these PGP traits and effects were tested on Mungbean. The selected isolates showed significant plant growth promotion with respect to increase in root length and number of secondary roots as compared to control. The relative gene expression analysis of three genes ARF (Auxin response factors), ERF (Ethylene-responsive factor 1), GAI (Gibberellic-Acid Insensitive), at a transcriptional level compared to control consortia 2 was better and also increased 5-7 folds in the juvenile root tissues of mungbean using qRT-PCR technique on 15th, 30th and 45th days of interval.